Production of local resource-based soil improvement materials as a community empowerment model in Sindangkasih Village, South Konawe - Syamsu Alam; Sahta Ginting; Halim Halim; Rachmawati Hasid; Namriah Namriah; La Ode Rustam; Rizki Pebriansyah (Community Empowerment, 2023)
Most of the residents in Sindangkasih Village earn their livelihoods through farming. The survey results indicate a decrease in the level of agricultural productivity in this village due to a lack of knowledge in agricultural management, leading to a continuous decline in soil fertility. Conversely, the village serves as a livestock center, producing cow dung waste, and houses a grain milling industry that generates rice husk waste, both of which have not been optimally utilized. The goal of this community service is to provide training and assistance to enhance the knowledge of farmer groups in producing soil improvement materials based on local resources. The methods employed in the service activities include counseling, demonstrations on creating soil improvement materials, and group discussions with the participation of 30 individuals. The results of the activity demonstrate an increase in the knowledge and skills of the Sindangkasih Village community in producing soil improvement materials, particularly organic fertilizer, to support agricultural production.